The impact of Mode 4 liberalization on bilateral trade flows - Marion Jansen; Roberta Piermartini (World Trade Organization (WTO), 2005)
This paper gives insights into the possible trade creating effects of service trade liberalization via Mode 4. In particular we expect that temporary movements of persons, like permanent movements, have the potential to reduce transaction costs for merchandise trade between home and host country. Exploiting data on H-1B beneficiaries from different origins in the United States and using a gravity model of trade, we find significantly positive effects of temporary movements of persons on bilateral merchandise trade. In addition to this, the paper provides insights into the determinants of temporary movements of persons.
Keywords: C30; F13; F15; F29; 330; Mode 4; bilateral trade flows; services liberalization; WTO; GATS